Land change dynamics in the Brazilian Cerrado: the interaction of biofuels, markets, and biodiversity - Granco, Gabriel (Kansas State University, 2017)
Biofuel ethanol has been proposed as the most viable solution to mitigate greenhouse gas emissions (GHG) from the transportation sector; however, the impact of such production on the environment is not completely known. Environmental impacts are of more concern when ethanol production occurs in areas of high biodiversity value such as the Cerrado (Brazilian savanna). The Cerrado is a global biodiversity hotspot and an important breadbasket—at the same time, it is on a path to becoming the major sugarcane ethanol-producing region in Brazil. The main goal of this dissertation is to examine the impacts of sugarcane expansion on farmers’ land use decision processes in the Cerrado and to consider its consequences on biodiversity and the impacts of climate change. In the following chapters, land change dynamics are investigated using a combination of theory and methods from geography, GIScience, economics, and ecology. Chapter 2 presents an examination of the drivers for the sugarcane expansion. The findings suggest that the Cerrado attracted mills because of the good agricultural conditions, affordable land prices, and favorable state-level fiscal incentive policies, while factors that have prevented traditional sugarcane-producing regions from meeting the increasing demand for ethanol. Chapter 3 develops a procedure to identify intensification and extensification responses at the field level. The main finding is that extensification is the main response. Additionally, this response has a higher probability of occurrence the farther an area is from a mill. Chapter 4 applies the partial adjustment framework to understand farmers’ land use decisions regarding sugarcane production. Estimates found that price of cattle have the largest cross-price elasticity with sugarcane acreage. In addition, the results suggest that acreage of sugarcane and soybean double-crop are positively correlated. Chapter 5 focuses on the impacts of climate change on land suitability for sugarcane and amphibian species. The findings show that land suitability for sugarcane is vulnerable to climate change and that the Brazilian zoning policy for sugarcane is not addressing this issue. Additionally, amphibians are affected by climate change and conflict with areas suitable for sugarcane in climate change scenarios.
Keywords: Geography; Land change science; Biofuel; Sugarcane; Brazil; Brazilian Cerrado (savanna)